Internet of things security : challenges, advances and analytics - Patel, Chintan; Doshi, Nishant (Boca Raton : CRC Press, Taylor & Francis Group, 2019)
This book focuses on the use of Elliptic Curve Cryptography with different authentication architectures and authentication schemes using various security algorithms to secure the Internet of Things. It also include mathematics from basic level to advance level required for security--
1. Internet of Things: An Overview. 2. A Mathematical Foundation. 3. IoT Authentication. 4. Single-Server Authentication. 5. Multi-Server Authentication Schemes. 6. Attacks and Remedies. 7. Analytical Matrices and Tools. 8. Future Work and Conclusion.
Includes bibliographical references and index.
CSE
Keywords: Internet of things -- Security measures; Computer science